Levels of mathematical ability of nursing students in various nursing schools in Manila : perspectives for instructional materials development - Soco, Luis L. (Manila : National University, 2007)
The Chinese General Hospital College of Nursing and Liberal Arts which is owned and managed by the Philippines Chinese Charitable Association was established in 1921 as the Chinese General Hospital School of Nursing.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.